Let's stay in touch - Evidence on the role of social learning in local tax interactions - Sebastian Blesse; Thorsten Martin (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper exploits detailed information on local political and socioeconomic networks and a reform of local fiscal equalization in North Rhine-Westphalia (NRW) to identify the role of learning in local tax rate interactions. Using this policy change in spatial lag IV regressions, we find that institutions like counties and jointly used administrations yield significant positive tax interactions whereas geographical neighbors do not react to each other. Common local media trigger tax policy interactions as well. Short-lived reform effects support our findings that social learning within certain networks intensifies tax rate interactions via coordination of local decision makers.
Keywords: H20; H71; H77; 330